2000
DOI: 10.1161/01.atv.20.1.198
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Offspring Is Associated With the Occurrence of Myocardial Infarction in First-Degree Relatives

Abstract: Abstract-The relevance of elevated levels of C-reactive protein (CRP) in cardiovascular disease is gaining increasing recognition. A family history of coronary artery disease is a major determinant of coronary artery disease in the offspring. In a cohort of 1048 individuals without clinical evidence of atherosclerosis, we investigated the relationships between CRP levels and a family history of myocardial infarction. We measured CRP, fibrinogen, plasminogen activator inhibitor-1, total cholesterol, triglycerid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 50 publications
(39 reference statements)
1
21
1
4
Order By: Relevance
“…12,13 Perhaps our results might help understand the link between raised levels of CRP and a family history of myocardial infarction. 34 The exact mechanism by which the CRP polymorphism influences CRP gene expression is not yet known, but logical models can be entertained. The GT low alleles could of course be in linkage with an as yet unidentified element(s) in the proximal promoter region of the CRP gene, and we are currently investigating this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Perhaps our results might help understand the link between raised levels of CRP and a family history of myocardial infarction. 34 The exact mechanism by which the CRP polymorphism influences CRP gene expression is not yet known, but logical models can be entertained. The GT low alleles could of course be in linkage with an as yet unidentified element(s) in the proximal promoter region of the CRP gene, and we are currently investigating this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between serum level of C-reactive protein (CRP) and blood pressure has been reported in several studies [12][13][14][15][16][17][18][19][20][21][22][23] (Table 1). This association is likely confounded by other risk factors, such as age, sex, and body mass index: Out of the six studies with no adjustment for potential confounders, [15][16][17][18][19]13 five [15][16][17][18][19] reported a statistically significant association between CRP and blood pressure (Table 1). Also, in a group of seven studies with adjustment for potential confounders, 12-24 four 24,22-24 reported a significant association between CRP and HBP.…”
Section: Epidemiologic Evidencementioning
confidence: 90%
“…Most of these studies [12][13][14][15][16][17][18][19][20][21][22] were not designed to test the CRP-HBP association. We tested this hypothesis in a random sample of free living subjects 23 and found a progressive increase in blood pressure associated to higher levels of high-sensitivity CRP.…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…These cytokines act locally or systemically. As a result of this complicated puzzle, the amount of TF in plasma increases via release from monocytes and neutrophils, circulatory platalets, endothelial cells or atherosclerotic plaque itself against the inflammatory response (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in CRP is a marker of recurring ischemia, MI and sudden cardiac death in patients with CAD (29). Increase in highly sensitive CRP indicates increased inflammatory state in the vascular wall (28).…”
Section: Discussionmentioning
confidence: 99%